2011
DOI: 10.1037/a0024210
|View full text |Cite
|
Sign up to set email alerts
|

Implicit measures of early-life family conditions: Relationships to psychosocial characteristics and cardiovascular disease risk in adulthood.

Abstract: Objectives An implicit measure of early-life family conditions was created to help address potential biases in responses to self-reported questionnaires of early-life family environments. We investigated whether a computerized affect attribution paradigm designed to capture implicit, affective responses (anger, fear, warmth) regarding early-life family environments was a) stable over time, b) associated with self-reports of childhood family environments, c) able to predict adult psychosocial profiles (perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
(100 reference statements)
2
15
0
Order By: Relevance
“…We also found that the childhood poverty effects on systolic but not diastolic blood pressure were mediated by exposure to family conflict. Prior work on social factors including childhood SES (71,72,73) as well as early family interpersonal relationships (74) reflect similar trends. It is not clear why systolic relative to diastolic blood pressure may be a more sensitive marker of stress outcomes to undesirable, early social conditions in life.…”
Section: Discussionmentioning
confidence: 83%
“…We also found that the childhood poverty effects on systolic but not diastolic blood pressure were mediated by exposure to family conflict. Prior work on social factors including childhood SES (71,72,73) as well as early family interpersonal relationships (74) reflect similar trends. It is not clear why systolic relative to diastolic blood pressure may be a more sensitive marker of stress outcomes to undesirable, early social conditions in life.…”
Section: Discussionmentioning
confidence: 83%
“…A general interpretive style characterized by heightened vigilance and suspicion of others may develop in the context of stressful and unpredictable childhood environments (Chen et al, 2004); our findings suggest that such an interpersonal orientation may persist later in life. In a recent study of implicit affect, attributions of anger and fear to one’s early childhood family environment were associated a greater tendency to perceived threat in response to ambiguous cues among adults (Chan et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Fifth, another limitation was the use of only one measure of threat vigilance in the present study. Even though we validated this measure in prior work (e.g., there were significant associations between threat vigilance assessed in the same manner and angry or fearful responses subsequent to viewing childhood family photographs; Chan et al, 2011), future studies could benefit from assessing threat vigilance at multiple levels of analysis within the same study (e.g., self-report, behavioral, psychophysiological, and neural measures) in order to replicate and extend our results.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study, test-retest reliability for this measure over a 1-month period was 0.79. This measure was previously validated with selfreport measures and shows correlations with other performance-based measures of implicit bias and cognitive control (Chan, Chen, Hibbert, Wong, & Miller, 2011;Payne, 2001Payne, , 2006.…”
Section: Methodsmentioning
confidence: 99%